2020
DOI: 10.4236/aim.2020.105017
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Essential Oil from <i>Citrus aurantifolia</i> (Christm.) Swingle Peels against Multidrug-Resistant Bacterial Isolates

Abstract: The study investigated the antibacterial activity of essential oil from the peel of Citrus aurantifolia against eleven multidrug-resistant (MDR) bacterial isolates of clinical origin. The Kirby-Bauer disc diffusion method was used to determine the antibiotic resistance profile of the isolates. Essential oil (EO) from the peels of lime purchased at a market in Ile-Ife was extracted by the hydro-distillation method, while the sensitivity of the isolates to EO was done via agar well diffusion method. The minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Te high antimicrobial activity of lime essential oil might be attributed to its high content of oxygenated organic compounds in comparison to the essential oils of grapefruit and orange and to the presence of nitrocompounds that are not detected in the other essential oils [30]. Te result of the present work of antimicrobial activity of Citrus sinensis was found to be comparable with that reported in numerous studies which investigated the antimicrobial efcacy of C. sinensis extract against a broad range of microorganisms.…”
Section: Grapefruitsupporting
confidence: 85%
“…Te high antimicrobial activity of lime essential oil might be attributed to its high content of oxygenated organic compounds in comparison to the essential oils of grapefruit and orange and to the presence of nitrocompounds that are not detected in the other essential oils [30]. Te result of the present work of antimicrobial activity of Citrus sinensis was found to be comparable with that reported in numerous studies which investigated the antimicrobial efcacy of C. sinensis extract against a broad range of microorganisms.…”
Section: Grapefruitsupporting
confidence: 85%
“…These chemical components contribute to its sharp aroma and antibacterial activity [27]. A previous study showed that the essential oil also exhibits broad-spectrum antibacterial activity [28].…”
Section: Discussionmentioning
confidence: 99%
“…Countries such as Brazil, the United States, Japan, China, Mexico, Pakistan, and the Mediterranean are the primary producers of citrus fruits [5]. On the other hand, as a native plant of tropical Asia, citrus is also widely used to treat various diseases [6][7][8]. Therefore, it has important implications in the world of trade and health sciences [9,10].…”
Section: Introductionmentioning
confidence: 99%